Modus Dan Mekanisme Kerusakan Perkerasan Lentur - M. Sjahdanulirwan; Nono Nono (Jurnal Jalan-Jembatan, 2005)
Increasing of the pavement life is cause deteration of pavement. Deteration is faster when there are over loading and the effect of unfriendly climate. This paper discusses of modus and mechanism of the defect occurring on flexible pavement and also recommendation of maintenance. Giving attention for example to type and quantity of defect, a maintenance program, and a suitable method of construction, can increase the effectively and efficiency of maintenance